2011
DOI: 10.5897/ajb11.532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tomato cultivars, honey finisher and processing methods on quality of tomato ketchup

Abstract: The experiment was carried out using factorial combination of two tomato varieties, two processing methods and three honey and one sugar concentrations with three replications. Tomato ketchups prepared from Melkashola subjected to pre-heat treatment before cooking exhibited higher total soluble solids, reducing and total sugars, as well as lower microbiological load. However, heat treatment significantly influenced the color of ketchups. Variety and processing methods significantly (P ≤ 0.01) affected the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Although tomato is a major agricultural product in Ethiopia, to date, little work has focused on identifying the key constraints and potentials on the system. So far, few studies have been made to address agronomic and pre-harvest management and postharvest treatment (Meaza et al, 2007;Temesgen et al, 2011;Meseret, 2010). Moreover, most research conducted on postharvest losses of tomato focused on market assessment (Abay, 2007;Adugna, 2009;Alemnew, 2010;Birhanu, 2011) and no extensive study has been done to identify post-harvest loss of tomato from farm gate to the point of consumption due to improper harvesting, post-harvest handling, transportation, intermediaries' malpractices, storage and other reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Although tomato is a major agricultural product in Ethiopia, to date, little work has focused on identifying the key constraints and potentials on the system. So far, few studies have been made to address agronomic and pre-harvest management and postharvest treatment (Meaza et al, 2007;Temesgen et al, 2011;Meseret, 2010). Moreover, most research conducted on postharvest losses of tomato focused on market assessment (Abay, 2007;Adugna, 2009;Alemnew, 2010;Birhanu, 2011) and no extensive study has been done to identify post-harvest loss of tomato from farm gate to the point of consumption due to improper harvesting, post-harvest handling, transportation, intermediaries' malpractices, storage and other reasons.…”
Section: Introductionmentioning
confidence: 99%
“…TSS of the tomato ketchup varies greatly as it depends on the formulation and especially presence of the thickening agents. The TSS content of tomato ketchup samples formulated with starch or CMC ranged from 21.3 to 30.3 °Brix (Temesgen et al, 2011). Ketchup prepared with different concentrations of sugar and salt had the TSS ranging from 19 to 35 (Minton, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Addition of honey to ketchup as preservation and sweetening agent provided significant increase in the TSS (Martínez-Tomé et al, 2003). Moreover, common salts added to formulation during ketchup processing affecting solubility of pectin causes an increase in the TSS (Temesgen et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Tomato is one of the most commonly cultivated and consumed vegetable fruit (Temesgen et al, 2011). Most cultivars produce red fruit but a number of cultivars with yellow, orange, pink, purple, green black and white fruits are also available (Peet, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of tomato products differ with respect to tomato cultivar (Temesgen et al, 2011). Opara et al (2012) reported changes in physicochemical properties and nutritional contents of three green house grown tomato cultivars.…”
Section: Introductionmentioning
confidence: 99%